2011
DOI: 10.1016/j.phrs.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril treatment discloses an early role of angiotensin II in inflammation- and oxidative stress-related muscle damage in dystrophic mdx mice

Abstract: Graphical abstractHighlights► An early treatment with enalapril was performed in exercised mdx mice. ► In vivo, enalapril increased mouse fore limb strength dose-dependently. ► Ex vivo, enalapril reduced muscular markers of oxidative stress and inflammation. ► Results corroborate an early role of angiotensin II in muscular dystrophy. ► Pre-clinical evidences of therapeutic interest of ACE inhibitors for therapy of DMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 44 publications
4
56
0
Order By: Relevance
“…At the end of experiments, samples were removed, cleaned from tendons, dried, and weighted. Absolute values of tension were normalized by cross-sectional area as previously described (6,11,14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of experiments, samples were removed, cleaned from tendons, dried, and weighted. Absolute values of tension were normalized by cross-sectional area as previously described (6,11,14).…”
Section: Methodsmentioning
confidence: 99%
“…In fact gCl reduction in mdx muscles is contrasted by anti-inflammatory agents, while tumor necrosis factor-␣ (TNF-␣), a key modulator of dystrophic muscle necrosis, partially decreases gCl via PKC activation (11,18,21,58). We recently observed that a treatment with enalapril, an inhibitor of the angiotensin-converting enzyme (ACE), while reducing the presence of markers of oxidative stress and inflammation in mdx mouse muscles, also leads to a dose-dependent restoration of gCl (14). This result lead us to hypothesize a possible role of angiotensin II (ANG II) signaling in ClC-1 channel modulation.…”
mentioning
confidence: 99%
“…39,40 The maintenance of a constant protocol of exercise and treatment was chosen in order to allow unbiased comparison of drug effects with those obtained in previous trials. 35 Control wild-type animals, age and gender-matched, underwent similar protocols and daily injection of vehicle (sterile water) as needed. Because of the well-described effect of exercise in the mdx phenotype, 36,39 the use of a group of sedentary mdx mice or wild-type exercised mice was not considered informative for the purpose of the present study and was regarded as unethical.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…Every week the animals were monitored for body weight and forelimb force, as described in detail elsewhere. 35 The values at the fourth week were used for statistical analysis. The treatment lasted 4-8 weeks, and the age of the animals at the time of killing was 2-3 months.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation